Transient Changes in Serum CEA, CA19-9, CRP, YKL-40, and IL-6 during Adjuvant Chemotherapy and Survival of Patients with Colorectal Cancer - Lehtomäki Kaisa; Heervä Eetu; Kellokumpu-Lehtinen Pirkko-Liisa; Mustonen Harri; Salminen Tapio; Joensuu Heikki; Hermunen Kethe; Boisen Mogens Karsbøl; Johansen Julia Sidenius; Haglund Caj; Osterlund Pia (MDPI, 2025)
Serum carcinoembryonic antigen (CEA) is frequently monitored to detect colorectal cancer (CRC) recurrence after surgery. The clinical significance of transiently increased CEA during adjuvant chemotherapy is poorly understood. Serum CEA, CA19-9, CRP, YKL-40, and IL-6 were measured before, during, and after adjuvant 5-fluorouracil-based chemotherapy in the randomised LIPSYT study population. The biomarker kinetic patterns were classified into three groups: no increase, a transient increase (≥10% increase followed by a decrease), and a persistent increase during the adjuvant treatment, and the associations of these patterns with disease free-survival (DFS) and overall survival (OS) were investigated by using Cox regression analyses. The findings were validated in two single-centre cohorts that received modern adjuvant chemotherapy. A transient increase in CEA occurred in about a half of the patients during chemotherapy, in all the cohorts. The patients with a transient increase had a roughly similar DFS and OS to the patients with no increase, and a more favourable survival compared to the patients with a persistent increase. In the LIPSYT cohort, the hazard ratio was 0.21 for DFS (CI95% 0.07-0.66) and 0.24 for OS (CI95% 0.08-0.76). Transient increases in CA19-9 and YKL-40 tended to be associated with a favourable survival. A transient increase in CEA during adjuvant chemotherapy is associated with a favourable survival when compared with a persistent increase.